2019
DOI: 10.1111/obr.12923
|View full text |Cite
|
Sign up to set email alerts
|

Childhood obesity intervention studies: A narrative review and guide for investigators, authors, editors, reviewers, journalists, and readers to guard against exaggerated effectiveness claims

Abstract: Being able to draw accurate conclusions from childhood obesity trials is important to make advances in reversing the obesity epidemic. However, obesity research sometimes is not conducted or reported to appropriate scientific standards. To constructively draw attention to this issue, we present 10 errors that are commonly committed, illustrate each error with examples from the childhood obesity literature, and follow with suggestions on how to avoid these errors. These errors are as follows:using self-reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 139 publications
(153 reference statements)
0
22
0
Order By: Relevance
“…A report from an American Society for Nutrition advisory committee highlighted the threats to research integrity that arise from competing interests among researchers, specifically the type of selective statistical analyses that are conducted and reported and the conclusions investigators draw from these (e.g., withholding unfavorable findings from publication) [ 3 ]. In a more detailed examination of such issues in the field of childhood obesity interventions, Brown et al identified ten statistical and methodological errors frequently found in the published literature that were associated with exaggerated claims about program effectiveness in changing diet, increasing exercise and weight reduction [ 4 ]. These included reporting results only for secondary outcome variables in the light of null findings for primary outcomes, reporting only subgroup analyses in the light of no main effects, data dredging for spurious statistically significant results, using one-tailed tests of statistical significance, and claiming that null results were nonetheless “clinically significant”.…”
Section: Introductionmentioning
confidence: 99%
“…A report from an American Society for Nutrition advisory committee highlighted the threats to research integrity that arise from competing interests among researchers, specifically the type of selective statistical analyses that are conducted and reported and the conclusions investigators draw from these (e.g., withholding unfavorable findings from publication) [ 3 ]. In a more detailed examination of such issues in the field of childhood obesity interventions, Brown et al identified ten statistical and methodological errors frequently found in the published literature that were associated with exaggerated claims about program effectiveness in changing diet, increasing exercise and weight reduction [ 4 ]. These included reporting results only for secondary outcome variables in the light of null findings for primary outcomes, reporting only subgroup analyses in the light of no main effects, data dredging for spurious statistically significant results, using one-tailed tests of statistical significance, and claiming that null results were nonetheless “clinically significant”.…”
Section: Introductionmentioning
confidence: 99%
“…cheek pressure (25.2%) when compared to a non-chewing exercise control group. Thus, the authors have countered for the random error influence [42].…”
Section: Orofacial Functionmentioning
confidence: 99%
“…In simple words, Takahashi and Satoh [38] found that the chewing gum group had a significant improvement in maximum tongue pressure (27.1%) and cheek pressure (25.2%) when compared to a non-chewing exercise control group. Thus, the authors have countered for the random error influence [42].…”
Section: Strength and Limitations Of The Included Studiesmentioning
confidence: 99%
“…Currently, there is wide variation in reporting of obesity intervention components; this makes evaluation and comparison across studies challenging. 13 For example, this review found limited or a lack of consistent information on descriptions of interventions, including how they were adapted, their reach, extent of stakeholder involvement, the role of context, or other elements that might influence equitable uptake. Systematic reporting to inform methods that enhance the adoption, implementation, and sustainability of interventions will allow for comparisons across studies and groups.…”
mentioning
confidence: 98%